Point of care detection of infection/inflammation in the diabetic clinic. (8th April 2022) - Levinson, Tal; Zehavi, Nir Tal; Berliner, Shlomo; Zeltser, David; Shapira, Itzhak; Shenhar-Tsarfaty, Shani; Wasserman, Asaf; Goldiner, Ilana; Rogowski, Ori; Shtark, Moshe
Introduction: Patients with diabetes are prone to infections. An elevated C-reactive protein (CRP) level indicates an underlying infection/inflammation; hence, a reliable point-of-care (POC) CRP measurement, independent of glucose level, would be advantageous in rapid detection of an inflammatory process and allowing for appropriate therapy in a timely manner. Methods: A validation study of patients with type 2 diabetes mellitus diagnosed with an inflammatory condition either infectious or non-infectious underwent a capillary CRP measurement on the same blood drop used for the measurement of capillary glucose level. Results: 154 samples from patients with diabetes across a broad range of CRP levels that underwent capillary CRP measurement, demonstrating a linear profile of the dynamic range compared with the wide range CRP assay, with significant correlation of R 2 = 0.9 and a slope of 0.98 (95% C.I: 0.91–1). Bland Altman analysis, presents a positive bias profile; the total difference between assays is 6.6 mg/L. The mean bias between methods is 13.34% (C.I 95% 9.8–17.5%). The total agreement between the methods is 89%, the observed Kappa index is: 0.71 with confidence interval of 0.57–0.84 indicating substantial agreement between the methods. C-reactive protein level is independent of glucose concentration. Conclusion: Point-of-care capillary CRP testing is a useful mean of early detection of infection/inflammation in patients with diabetes and enables the treating physician to rapidly assess and treat the patients underlying inflammatory process.